Altered expression of the WT1 Wilms tumor suppressor gene in human breast cancer - Silberstein, Gary B. (The National Academy of Sciences of the USA, 1997)
The product of the WT1 Wilms tumor suppressor gene controls the expression of genes encoding components of the insulin-like growth factor and transforming growth factor β signaling systems. The role of these growth factors in breast tumor growth led us to investigate possible WT1 gene expression in normal and cancerous breast tissue. WT1 was detected by immunohistochemistry in the normal mammary duct and lobule, and the patterns of expression were consistent with developmental regulation. In a survey of 21 infiltrating tumors, 40% lacked immunodetectable WT1 altogether and an additional 28% were primarily WT1-negative. Cytoplasmic, but not nuclear, localization of WT1 was noted in some tumor cells and WT1 was detected, sometimes at high levels, in more-advanced estrogen-receptor-negative tumors. In this highly malignant subset, the tumor suppressor protein p53, which can physically interact with WT1, was also sometimes detected. WT1 mRNA was detected in normal and tumor tissue by reverse transcription-coupled PCR. Alternative splicing of the WT1 mRNA may regulate gene targeting of the WT1 protein through changes either in its regulatory or zinc-finger domains. The relative proportions of WT1 mRNA splice variants were altered in a random sample of breast tumors, providing evidence that different tumors may share a common WT1-related defect resulting in altered regulation of target genes.